Three-dimensional light manipulation by gold nanobumps - Chang, Chia Min (2014)
The scattering of surface plasmon polariton (SPP) waves can be manipulated by various plasmonic structures. The plasmonic structure composed of arranged subwavelength nanobumps on a gold thin film is the promising structure to manipulation SPP wave. By controlling the geometric shape of the structures, the height, position, and pattern of scattered light from SPP wave can be modulated as desired. A clear single focusing spot can be reconstructed at a specific altitude by a particular curved structure with appropriate curvature and adjacent interspacing of nanobumps. The designed light patterns reconstructed by the focusing spot from the arranged curved structures at a specific observation plane are clearly demonstrated.